2021
DOI: 10.3390/polym13162626
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate/Poly(vinylidene fluoride)-Blend-Based Nanocomposites—Effect of Adding Different Carbon Nanofillers/Organoclay

Abstract: Carbon black (CB), carbon nanotubes (CNTs), and graphene nanoplatelets (GnPs) individually or doubly served as reinforcing fillers in polycarbonate (PC)/poly(vinylidene fluoride) (PVDF)-blend (designated CF)-based nanocomposites. Additionally, organo-montmorillonite (15A) was incorporated simultaneously with the individual carbon fillers to form hybrid filler nanocomposites. Microscopic images confirmed the selective localization of carbon fillers, mainly in the continuous PC phase, while 15A located in the PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The tensile modulus of PC/MXD6/PET‐CB (70/15/15‐2) composite is 1948 MPa, which increases by 26.3% compared with that of PC/MXD6/PET blend. It has been reported that the moduli of PC/acrylonitrile–butadiene–styrene (45/55 w/w) and PC/PVDF (7/3 vol/vol) also increase after incorporating CB 59,60 . The improvement in tensile modulus in the case of PC/MXD6/PET‐CB (70/15/15‐2) composite can be attributed to the formation of sea‐island type interfacial CB network and the resulted continuity of the PET phase, which increase elasticity of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile modulus of PC/MXD6/PET‐CB (70/15/15‐2) composite is 1948 MPa, which increases by 26.3% compared with that of PC/MXD6/PET blend. It has been reported that the moduli of PC/acrylonitrile–butadiene–styrene (45/55 w/w) and PC/PVDF (7/3 vol/vol) also increase after incorporating CB 59,60 . The improvement in tensile modulus in the case of PC/MXD6/PET‐CB (70/15/15‐2) composite can be attributed to the formation of sea‐island type interfacial CB network and the resulted continuity of the PET phase, which increase elasticity of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The large dimension of the GNP layers was more successful than rod-shaped CNT in acting as a thermal shield and preventing the evaporation of the degraded components. 71 The moisture content of the aerogel nanocomposites can be estimated from the value of the first weight loss. Based on the results presented in Table 3, the PVTMS has the highest moisture content among all of the samples.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Specifically, the LEP of M1, M2, M3, and M4 were 310 ± 7 kPa 280 kPa ± 3, 340 kPa ± 6, and 330 kPa ± 1, respectively. According to Chiu et al (2021), addition of f-CNTs increases viscosity of PVDF polymer solution, thus leading to a decreased exchange rate of the solvent (DMac/DMF 3:2) and non-solvent (water) during phase inversion (Chiu et al, 2021). Decreased solvent exchange rate reduced overall membrane porosity and pore size (Table 2).…”
Section: Physical Properties Of Pvdf Membranesmentioning
confidence: 99%